PENERAPAN KURIKULUM MERDEKA PADA GURU PJOK DI SD NEGERI 187 PEKANBARU - Fahrozi, Fahrul; Juita, Ardiah; Aspa, Agus Prima (Ensiklopedia of Journal, 2024)
This research aims to investigate the implementation of the Independent Curriculum among Physical Education, Sports and Health (PJOK) teachers at SD Negeri 187 Pekanbaru. The research method used is descriptive qualitative, with a focus on understanding and interpreting individual experiences to understand social reality. The results of the research show that SD Negeri 187 Pekanbaru has implemented the Independent Curriculum in its learning, with classes I, II, IV and V using this curriculum. However, obstacles such as lack of special training for teachers, students' difficulties in understanding learning, and limited facilities and infrastructure are still faced. However, the use of the Independent Curriculum in schools has given educators the freedom to implement more creative and student-centered learning. The conclusion of this research emphasizes the need for more attention from the government to overcome these obstacles so that the Independent Curriculum can be implemented well without obstacles in the future. Keywords: PJOK, descriptive qualitative, independent curriculum.